Aprendizagem ativa em um curso de Engenharia de Produção: percepções dos docentes e discentes e mudanças curriculares - Turrioni, Ana Maria Silveira (2017)
The objective of this research was to identify how the use of active learning affects the students, the professors and the curriculum of a course of Industrial Engineering. The expansion of this area in Brazil, together with the evolution of digital information and communication technologies, leads to an increase in the complexity of teaching in this field, justifying the analysis of the consequences of using this approach. The proposed hypothesis is that the use of active learning affects the behavior of students and teachers generating a new curricular proposal.To analyze this phenomenon, I opted for Action Research, since I was able to observe it during the development of the research, actively participating in the actions. I collaborated in the planning of the Semester Project discipline, in the organization of internal dissemination events, in the training of professors and in the reflection on the achieved results.The data were collected through participant observations, questionnaire applied to the students, interviews with professors, personal insights and documentary analysis. The main results obtained were the strengthening of students' skills and abilities, professor training, university and business cooperation, the development of infrastructure for the use of active learning and professor participation in the construction of a curriculum for the Industrial Engineering course shaped for its social and cultural reality